CHANGES IN THE STRUCTURE OF DONORS AND DONATIONS OF BLOOD AND ITS COMPONENTS IN THE REPUBLIC OF UZBEKISTAN - Samatova L. D.; Saidov A.B.; Bobojonova Sh. D. (Innovate Conferences, 2025)
The blood service is a vital component of healthcare, providing the opportunity to provide high-tech specialized medical care using a unique national resource - donor blood, both in peacetime and in emergency situations. The safety and effectiveness of blood transfusion remains a cornerstone of modern medicine, reflecting the collective efforts of dedicated individuals who generously donate their blood to save the lives of health care workers, researchers and others. The purpose of the blood service is to ensure the quality of transfusion therapy. To achieve this goal, the institution is divided into blood service specialists, i.e. medical workers and public organizations involved in the production, transportation and storage of blood and its components, and specialists clinically applying alternative technologies of allogeneic blood transfusion, and they work together. An important condition for participation in donation is that the donor's health meets certain medical criteria. The problem of donor blood and its components is considered important for the state and is key in the country's health care. The quality and availability of high-tech medical care in peacetime and emergency situations depend on the effective resolution of donation issues at the regional level. A positive attitude of society towards charity and active participation of the population correspond to the goals of the state in the sphere of security and the socio-political sphere - the formation of a healthy generation, a physically and spiritually strong society. Improvement of specialized medical care, primarily in oncology, hematology, cardiac surgery, traumatology, obstetrics and other specialties, causes an increase in the need of medical institutions for blood components, the only source of which are donors. Therefore, donors should lead a healthy lifestyle, give up bad habits and take care of their health.